2013
DOI: 10.1089/bfm.2012.0003
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding Plan of Pregnant Southeast Asian Women: What Encourages Them?

Abstract: Planning of prolonged breastfeeding has little to do with maternal age, education, or number of pregnancies. However, mothers who work, who had previously breastfed for a short period, and who are not well informed about breastfeeding tend to plan shorter breastfeeding. Among mothers who work, it is the length of maternal leave and required working hours that determine the plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Similar to other studies [28, 29], the current study did not find association between EBF up to six months and the following mother’s socio-demographic characteristics: age, level of education, marital status, family income, occupation, and parity. Given that the study had sufficient power (1.00), this finding can be explained by the fact that the association between these factors and breastfeeding practice is influenced by others factors.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other studies [28, 29], the current study did not find association between EBF up to six months and the following mother’s socio-demographic characteristics: age, level of education, marital status, family income, occupation, and parity. Given that the study had sufficient power (1.00), this finding can be explained by the fact that the association between these factors and breastfeeding practice is influenced by others factors.…”
Section: Discussionsupporting
confidence: 88%
“…Factors like maternal knowledge and attitude, burden of work, receipt of breastfeeding education, and literacy levels significantly impact maternal decision to exclusively breastfeed. [16][17][18][19][20] The cultural practice of giving prelacteal is widely prevalent in India 21 and its neighbouring countries. 22,23 Our study, in consonance with previous studies, also found that use of prelacteal feed was widely prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…7,34,35 It is not surprising to find in our analysis that returning to work was a significant barrier to exclusive breastfeeding, which was revealed in many previous studies. 5,[35][36][37] Lack of support from workplace or unfavorable working conditions may compel working mothers to consider early termination of breastfeeding exclusivity and introduction of formula during or immediately after the maternity leave. 38,39 Policy initiatives and resources to promote work environments conducive to breastfeeding may effectively increase the rate of exclusive breastfeeding among working mothers.…”
Section: Discussionmentioning
confidence: 99%